S∗p‐b-Partial Metric Spaces with some Results in Common Fixed Point Theorems - A. M. Zidan (Journal of Function Spaces)
In this paper, we introduce the notion of S∗P‐b-partial metric spaces which is a generalization each of S‐b-metric spaces and partial-metric space. Also, we study and prove some topological properties, to know the convergence of the sequences and Cauchy sequence. Finally, we study a new common fixed point theorem in these spaces.